Fire and Mechanical Properties of Hemp and Clay Boards for Timber Structures. (June 2019) - Kallakas, H; Liblik, J; Alao, P F; Poltimäe, T; Just, A; Kers, J
Abstract: The use of timber with other bio-based building materials is often restricted due to the fire hazard. The primary protection for timber against fire is provided by cladding. Currently, there is limited fire protection design data on clay and hemp boards since they are relatively new products. Furthermore, the mechanical performance of boards is of utmost importance in timber frame assemblies. This paper presents a test program that determines the tensile and bending strength of boards accompanied by a comparison to widely used gypsum plasterboards. The fire protection effect for timber is assessed by using a cone heater. Main results indicate that clay and hemp boards are adequate alternatives for the gypsum plasterboards as they can demonstrate similar performance. Hemp boards made by dry method perform significantly better compared to the ones made by wet method. Clay boards with special additive demonstrate increased fire performance compared to more ecological boards. This study contributes to further research that is needed in order to provide design parameters for sustainable building solutions in the future.